Identification of Human DNA in Mixture of Human and Chicken Blood Using PCR with Specific Primer of Cytochrome B Gene - Widodo, Wimbuh Tri; Yudianto, Ahmad; Wahyuningsih, Astuti (Folia Medica Indonesiana, 2018)
This study aimed to identify human DNA from mixing human and chicken blood samples by utilizing Polymerase Chain Reaction (PCR) and cytochrome b gene primer. The cytochrome b gene is a gene located in mitochondrial DNA and has high variation of sequence relation between one species and another. PCR analysis was performed using human cytochrome b gene primer in variation of DNA templates (0 ng, 0.01 ng, 0.1 ng, 1 ng, 10 ng and 100 ng), human blood percentages (100%, 50%, 40 %, 25%, 10%, 5%, 1%, 0%) and sample age before analysis (0 day, 3 days, 7 days, 10 days, and 15 days). The minimum DNA template obtained in this study was 0.01 ng and minimum percentage of human blood in the mixture was 1%. Blood spots on cloth isolated on days 0, 3, 7, 10 and 15 could still be analyzed and the resulting of DNA band (157 bp) had the same intensity/thickness. From the results of this study, it can be concluded that human blood in the mixture of human and chicken blood can be identified using PCR with specific primers of cytochrome b gene. PCR using specific primer of cytochrome b gene may help forensic practitioners to identify human sample in mixed biological samples.